2018
DOI: 10.1007/s10620-018-5036-1
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory and Antioxidant Effects of Captopril Compared to Methylprednisolone in l-Arginine-Induced Acute Pancreatitis

Abstract: Captopril treatment showed a protective and comparable effect with MP treatment in AP rat model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 37 publications
1
21
0
Order By: Relevance
“…Several studies demonstrated that ACE inhibitors prevent a wide variety of key events, among them anti‐inflammatory effects. In this context, the possible protective role of captopril as anti‐inflammatory and antioxidant in pancreatic inflammation was investigated, whose captopril showed a significant reduction in pancreatic TNF‐α concentration [28] . Besides, a captopril study investigates the ability to attenuate the cardiac inflammatory process associated with arterial hypertension, showing the inflammation process decrease in the left ventricle of hypertensive rats through an activation reduction of pro‐inflammatory factors [29]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies demonstrated that ACE inhibitors prevent a wide variety of key events, among them anti‐inflammatory effects. In this context, the possible protective role of captopril as anti‐inflammatory and antioxidant in pancreatic inflammation was investigated, whose captopril showed a significant reduction in pancreatic TNF‐α concentration [28] . Besides, a captopril study investigates the ability to attenuate the cardiac inflammatory process associated with arterial hypertension, showing the inflammation process decrease in the left ventricle of hypertensive rats through an activation reduction of pro‐inflammatory factors [29]…”
Section: Resultsmentioning
confidence: 99%
“…In this context, the possible protective role of captopril as anti-inflammatory and antioxidant in pancreatic inflammation was investigated, whose captopril showed a significant reduction in pancreatic TNF-α concentration. [28] Besides, a captopril study investigates the ability to attenuate the cardiac inflammatory process associated with arterial hypertension, showing the inflammation process decrease in the left ventricle of hypertensive rats through an activation reduction of pro-inflammatory factors. [29] Finally, the Cuphea species are reported with antiinflammatory and antihypertensive potential and have a great diversity of flavonols derivatives as quercetin.…”
Section: Peak [A]mentioning
confidence: 99%
“…Captopril is an angiotensin-converting enzyme inhibitor (ACEI) that is widely used for hypertension management. Other potential effects of captopril have also been reported, including antioxidation, anti-inflammation, cardio-protection, and vasodilation [ 32 , 33 , 34 ]. In this study, captopril was used as a positive control agent.…”
Section: Introductionmentioning
confidence: 99%
“…Although AP may have different etiologies, the clinical presentation typically includes auto-degeneration of the tissue upon the activation of pancreatic enzymes and the consequent infl ammation caused by the release of such key pro-infl ammatory cytokines as interleukins (ILs) and tumor necrosis factor-alpha (TNF-α) (2). TNF-α promotes infl ammatory cells infi ltration including neutrophils and macrophages to accumulate in the pancreas, which results in exacerbating the local infl ammatory response in the pancreas and progressing into a systemic infl ammatory response (3).…”
Section: Introductionmentioning
confidence: 99%